1997
DOI: 10.1042/bj3230661
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli l-aspartate-α-decarboxylase: preprotein processing and observation of reaction intermediates by electrospray mass spectrometry

Abstract: The Escherichia coli panD gene, encoding l-aspartate-alpha-decarboxylase, was cloned by PCR, and shown to complement a panD mutant defective in beta-alanine biosynthesis. Aspartate decarboxylase is a pyruvoyl-dependent enzyme, and is synthesized initially as an inactive proenzyme (the pi-protein), which is proteolytically cleaved at a specific X-Ser bond to produce a beta-subunit with XOH at its C-terminus and an alpha-subunit with a pyruvoyl group at its N-terminus, derived from the serine. The recombinant en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
98
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(103 citation statements)
references
References 29 publications
(52 reference statements)
4
98
1
Order By: Relevance
“…The resulting kinetic parameters showed that the K M values determined in this manner agree well with those reported for the EcADC and MtADC enzymes as determined by indirect assay methods, whereas the k cat values were approximately tenfold lower than the previously reported values (see the Supporting Information for details). [8,20] This result showed that although the sensitivity of the enzyme-coupled assay is lower than could be desired, it can successfully be used to determine the decarboxylation activity of the respective ADC enzymes.…”
Section: Catalytic Activity Assaysmentioning
confidence: 90%
See 2 more Smart Citations
“…The resulting kinetic parameters showed that the K M values determined in this manner agree well with those reported for the EcADC and MtADC enzymes as determined by indirect assay methods, whereas the k cat values were approximately tenfold lower than the previously reported values (see the Supporting Information for details). [8,20] This result showed that although the sensitivity of the enzyme-coupled assay is lower than could be desired, it can successfully be used to determine the decarboxylation activity of the respective ADC enzymes.…”
Section: Catalytic Activity Assaysmentioning
confidence: 90%
“…We chose this assay over previous methods that have been used to measure ADC activity because these were nearly all based on derivatization of the substrate and product mixtures with fluorescamine followed by HPLC analysis. [8,20] We were concerned that the introduced fluorine (and the concomitant effect it has on the basicity and nucleophilicity of the amine) may influence the extent and rate of derivatization, which would lead to inaccurate activity determinations. In contrast, a CO 2 -release assay would not suffer from such a drawback, and should respond similarly to both the natural and fluorinated aspartates.…”
Section: Catalytic Activity Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of aspartate, [1,2,3,4-13 C 4 ]L-aspartate was found to serve as the precursor for all the carbons of ␤-alanine, which indicates that an ␣-decarboxylase could be responsible for generating ␤-alanine from L-aspartate. The canonical enzyme for catalyzing this reaction for coenzyme A biosynthesis is a pyruvoyldependent decarboxylase (15), but a gene encoding this enzyme is absent in the genome of M. jannaschii.…”
Section: Discussionmentioning
confidence: 99%
“…A likely alternate substrate for pantoic acid biosynthesis in the methanogens would be 5,10-methylene-tetrahydromethanopterin, since this cofactor can function in an analogous manner as 5,10-methylene-tetrahydrofolate as demonstrated by its involvement in serine metabolism using the archaeal version of serine hydroxymethyltransferase (14). Figure 2 shows the six known routes or pathways for the biosynthesis of ␤-alanine and include the following: pathway 1, the decarboxylation of L-aspartate (15); pathway 2, the transamination between malonate semialdehyde and L-glutamate (16) or Lalanine (17); pathway 3, the hydrolysis of dihydrouracil produced by the hydrogenation of uracil (18); pathway 4, the oxidative cleavage of spermine to 3-aminopropanal followed by the oxidation of the aldehyde of this molecule to a carboxylic acid (19); pathway 5, the action of an 2,3-aminomutase on alanine (20); and pathway 6, the addition of ammonia to acryloyl-CoA, followed by the hydrolysis of the CoA thioester (21). In each of these cases, except the transamination reaction, the enzyme(s) involved in catalyzing each specific reaction is known.…”
mentioning
confidence: 99%